THE IMPACT OF THE "PHASED" APPROACH THE REHABILITATION OF PHYSICAL EDUCATION ON THE LEVEL OF CELL REACTIVITY OF CHILDREN WITH VISUAL IMPAIRMENTS - Vasilevsky, V.S.; Dіchko, D.V.; Dіchko, V.V.; Popkov, Y. (World of Medicine and Biology, 2016)
In our research it was found bilateral changes in the absolute and relative amounts of the major populations of immune cells, erythrocytes, The rehabilitation activities we have developed a method that aims to improve the physical development of these children and the improvement of adaptive-compensatory capabilities, enhanced cellular and immunological reactivity of children aged 10-16 years, with visual impairments.
Keywords: adolescents with disorders of view; the complex of rehabilitation measures; cellular reactivity; an indicator of intoxication; erythrocyte sedimentation rate